Histopathologic differences in granulomas of Mycobacterium bovis bacille Calmette Guérin (BCG) vaccinated and non-vaccinated cattle with bovine tuberculosis - Kanipe, C.; Boggiatto, P. M.; Putz, E. J.; Palmer, M. V. (Frontiers in Microbiology, 2022)
Mycobacterium bovis (M. bovis) is the zoonotic bacterium responsible for bovine tuberculosis. An attenuated form of M. bovis, Bacillus Calmette-Guerin (BCG), is a modified live vaccine known to provide variable protection in cattle and other species. Protection for this vaccine is defined as a reduction in disease severity rather than prevention of infection and is determined by evaluation of the characteristic lesion of tuberculosis: the granuloma. Despite its recognized ability to decrease disease severity, the mechanism by which BCG imparts protection remains poorly understood. Understanding the histopathologic differences between granulomas which form in BCG vaccinates compared to non-vaccinates may help identify how BCG imparts protection and lead to an improved vaccine. Utilizing special stains and image analysis software, we examined 88 lymph nodes obtained from BGC-vaccinated and non-vaccinated animals experimentally infected with M. bovis. We evaluated the number of granulomas, their size, severity (grade), density of multinucleated giant cells (MNGC), and the amounts of necrosis, mineralization, and fibrosis. BCG vaccinates had fewer granulomas overall and smaller high-grade granulomas with less necrosis than non-vaccinates. The relative numbers of high- and low- grade lesions were similar as were the amounts of mineralization and the density of MNGC. The amount of fibrosis was higher in low-grade granulomas from vaccinates compared to non-vaccinates. Collectively, these findings suggest that BCG vaccination reduces bacterial establishment, resulting in the formation of fewer granulomas. In granulomas that form, BCG has a protective effect by containing their size, reducing the relative amount of necrosis, and increasing fibrosis in low-grade lesions. Vaccination did not affect the amount of mineralization or density of MNGC.